PENGARUH KESADARAN MEREK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KOPI (STUDI KASUS PADA KONSUMEN KEDAI KOPI AZHAR) - Edi Purwanto; Rum Marhaki; Santosa Tri Prabawa (ITB AAS Indonesia Surakarta, 2023)
The development of lifestyle patterns and business competition today, especially in the coffee sector, has encouraged researchers to conduct research that aims to determine the effect of brand awareness, price, and location on coffee purchasing decisions at the Azhar Delanggu Coffee shop. The population in this study were 150 people who had consumed products from the Azhar Coffee shop. Using a simple random sampling method with a sample size of 60 respondents. Methods of collecting data using questionnaires and data processing using multiple regression analysis assisted by the SPSS 25 program. The results of the study conclude that brand awareness and price affect purchasing decisions, while location has no effect on purchasing decisions. Keywords : Brand awareness, price, location, purchasing decisions.